Neuroendocrine and metabolic predictors of the effects of balneotherapy at the Truskavets Spa on physical working capacity in men with maladaptation - Popovych, Igor L.; Zukow, Walery; Melnyk, Oksana I.; Fil, Vitalii M.; Kovalchuk, Halyna Y.; Bryndzia, Iryna V.; Voloshyn, Olena R.; Kopko, Iryna Y.; Lupak, Oksana M.; Skrobach, Taras B.; Kravtsiv Mariana М.; Musiyenko, Olena V.; et al. (European Journal of Clinical and Experimental Medicine, 2025)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. The effect of balneotherapy in the Truskavets Spa on physical working capacity is complex and individ ualized. This study aims to identify an optimal constellation of predictors for the actotropic effects of balneotherapy. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. We observed 34 men with maladaptation against the background of chronic pyelonephritis in remis sion. We recorded physical working capacity, heart rate variability, electroencephalography, adaptation hormones, and blood and urine metabolites before and after a standardized balneotherapy regimen. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Standard balneotherapy resulted in various effects on physical working capacity150 : an increase in 9 patients (26.5%), no significant change in 16 patients (47.1%), and a decrease in 9 patients (26.5%). Through discriminant analysis, we identified a constellation of 25 initial parameters that could predict the nature of the actotropic effect with 100% accuracy. These parameters included measures of physical working capacity, cardiorespiratory fitness, electroencephalography, heart rate variability, hormones, and metabolism. Furthermore, multiple linear regression analysis allowed us to predict quantitative changes in physical work capacity150 with a standard error of 0.28 W/kg. This predictive model incorporated hemodynamic and Electroen cephalography parameters, achieving an adjusted R2 of 0.555. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. The directionality and magnitude of physical working capacity150 changes under the influence of balneofactors at the Truskavets Spa are determined by a complex constellation of initial physiological parameters, which forms the body’s reactivity. This finding has significant implications for personalizing balneotherapy treatments.